Global, Regional, and National Burden of Myocarditis and Cardiomyopathy, 1990–2017 - Dai, Haijiang; Lotan, Dor; Much, Arsalan Abu; Younis, Arwa; Lu, Yao; Bragazzi, Nicola Luigi; Wu, Jianhong (Frontiers in Cardiovascular Medicine, 2021)
Objective: To estimate the burden of myocarditis (MC), alcoholic cardiomyopathy (AC) and other cardiomyopathy (OC) for 195 countries and territories from 1990 to 2017. Methods: We collected detailed information on MC, AC and OC between 1990 and 2017 from the Global Burden of Disease study 2017. All estimates were presented as counts, age-standardised rates per 100 000 people and percentage change, with 95% uncertainty intervals (UIs). Results: Worldwide, there were 1.80 million (95% UI 1.64 to 1.98) cases of MC, 1.62 million (95% UI 1.37 to 1.90) cases of AC and 4.21 million (95% UI 3.63 to 4.87) cases of OC, contributing to 46 486 (95% UI 39 709 to 51 824), 88 890 (95% UI 80 935 to 96 290) and 233 159 (95% UI 213 677 to 248 289) deaths in 2017, respectively. At the national level, the age-standardised prevalence rates varied by 10.4 times for MC, 252.6 times for AC and 38.1 times for OC; and the age-standardised death rates varied by 43.9 times for MC, 531.0 times for AC and 43.3 times for OC. Between 1990 and 2017, despite the decreases in age-standardised rates, the global numbers of prevalent cases and deaths have significantly increased for all the diseases. Conclusion: MC, AC and OC remain important global public health problems, and there are significant geographic variations in the burden of these diseases. Further research is warranted to expand our knowledge of potential risk factors and to improve the prevention, early detection and treatment of these diseases.